Incontinentia pigmenti: a case report and literature review - Emre, Sinan; Firat, Yezdan; Güngör, Serdal; Firat, Ahmet Kemal; Karincaoğlu, Yelda (The Turkish Journal of Pediatrics, 2009)
Incontinentia pigmenti (IP) is a rare, X-linked dominant disorder that presents at or soon after birth with characteristic cutaneous signs. The eyes and central nervous system are the next most commonly affected systems. We aimed to describe the ophthalmological, neurological and radiodiagnostic findings of a patient with IP and bilateral retinal detachment. Clinical and laboratory findings of a four-month-old female baby who did not have light fixation and had neurological maturation retardation are presented. Characteristic skin lesions of IP were noted especially at the extremities, bilaterally. On neurological examination, motor and mental maturation were retarded and axial hypotonia was noted. Bilateral retinal detachment was the cause of absent eye fixation noted during ophthalmologic examination, and the detachments were also documented by ultrasonography and magnetic resonance imaging (MRI). Otologic examination was normal. Focal left frontal lobe atrophy, corpus callosum hypoplasia and prominence of right hemisphere were also noted on MRI. MR spectroscopy revealed negative lactate peak at the involved left frontal lobe. Bilateral retinal detachment is a probable finding in IP and patients with neurological symptoms should be investigated for associated sight-threatening ocular pathologies.